2020
DOI: 10.26434/chemrxiv.12071508.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Flavonoids as 2019-nCoV Cell Entry Inhibitor Through Molecular Docking and Pharmacological Analysis

Abstract: In this study we aimed at the receipt binding domain of S protein and ACE-2 receptor as a promising drug targets against SARS-CoV-2. Flavonoids with anti-viral properties were taken as ligand for molecular docking. Selected flavonoids showed extremely good pharmacokinetics properties with good absorption, solubility, metabolism, excretion,distribution, bioavailability and minimal toxicity. These identified lead flavonoids may act as potential compound for the development of effective drugs and may help in cont… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…Recent research teams characterized the interaction site of the S protein of the SARS‐CoV‐2 virus and revealed that flavonoids can bind ACE2, regulate the ACE1 and ACE2 levels, and maintain their basal levels (Bhowmik, Nandi, Prakash, & Kumar, 2021; Derosa, Maffioli, D'Angelo, & Di Pierro, 2021; El‐Missiry, Fekri, Kesar, & Othman, 2021; J. Gao et al, 2021; Gour, Manhas, Bag, Gorain, & Nandi, 2021; H. Chen & Du, 2020; Cherrak, Merzouk, & Mokhtari‐Soulimane, 2020; Khan et al, 2021; Mendonca & Soliman, 2020; Muchtaridi, Fauzi, Ikram, Gazzali, & Wahab, 2020; Omotuyi et al, 2021; Russo, Moccia, Spagnuolo, Tedesco, & Russo, 2020; Tutunchi, Naeini, Ostadrahimi, & Hosseinzadeh‐Attar, 2020; J. W. Yu, Wang, & Bao, 2020). In addition, disruption of the interaction between ACE2 and the SARS‐CoV‐2 spike protein is the main effect of flavonoids.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Recent research teams characterized the interaction site of the S protein of the SARS‐CoV‐2 virus and revealed that flavonoids can bind ACE2, regulate the ACE1 and ACE2 levels, and maintain their basal levels (Bhowmik, Nandi, Prakash, & Kumar, 2021; Derosa, Maffioli, D'Angelo, & Di Pierro, 2021; El‐Missiry, Fekri, Kesar, & Othman, 2021; J. Gao et al, 2021; Gour, Manhas, Bag, Gorain, & Nandi, 2021; H. Chen & Du, 2020; Cherrak, Merzouk, & Mokhtari‐Soulimane, 2020; Khan et al, 2021; Mendonca & Soliman, 2020; Muchtaridi, Fauzi, Ikram, Gazzali, & Wahab, 2020; Omotuyi et al, 2021; Russo, Moccia, Spagnuolo, Tedesco, & Russo, 2020; Tutunchi, Naeini, Ostadrahimi, & Hosseinzadeh‐Attar, 2020; J. W. Yu, Wang, & Bao, 2020). In addition, disruption of the interaction between ACE2 and the SARS‐CoV‐2 spike protein is the main effect of flavonoids.…”
Section: Flavonoidsmentioning
confidence: 99%
“…The high reactivity of the resorcinol structure is primarily associated with the location of these two hydroxyl groups in the benzene ring [110]. The resorcinol moiety of ring A might play a role in ACE2 inhibition, as this group might disrupt hydrogen bonds between Glu329/Gln325 of ACE2 and Arg426 of the S protein of SARS CoV-2, which form a salt bridge to stabilize their interaction [72,73].This hydrophobic interaction occurs in ring C with some non-polar amino acid residues such as Gly354, Asp355, and Phe356 [111].…”
Section: Flavonoids As Ace2 Inhibitorsmentioning
confidence: 99%
“…Crystal structure modeling of both ACE-2 and SARS-CoV-2 S protein has identified flavonoids, a subgroup of phenolic compounds, as suitable candidates for binding and inhibiting both molecules in silico [60]. Assessment has started on these compounds in vitro, and there are successes showing SARS-CoV-2 inhibition with phenolic compounds also effective against SARS-CoV [61,62].…”
Section: Blocking the Sars Viruses Connection With Ace-2mentioning
confidence: 99%